Determinants of SMEs Performance in Pakistan: A Pilot Study - Tariq, Tamoor Ali; Lazim, Halim bin Mad; Iteng, Rosman bin (South Asian Journal of Social Sciences and Humanities, 2021)
This study’s main objective is to investigate the face validity and reliability of the determinants of SMEs’ performance in Pakistan. For this purpose, researchers adopted a simple random sampling approach to collect a small data sample from the Owners/managers of 41 individual manufacturing SMEs. The model suggested four factors (PDI, PCI, OLC, TO) as the determinants of SMEs performance. Therefore, the instruments’ reliability and validity were keenly examined with experts from academia and industry. Moreover, collected data were processed and analysed by using SPSS. However, the results of the study established the face validity and reliability of the adapted instruments.